1951
DOI: 10.1111/j.1365-2621.1951.tb17359.x
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF METHODS OF PREPARING FOOD PRODUCTS FOR MICROBIOLOGICAL ANALYSES1

Abstract: The method of preparing food products for analysis is of considerable importance, since the resulting counts of microorganisms obtained depend to a large extent on the effectiveness of mixing and agitation in freeing the organisms from the surface. The usual method of preparing products for analysis usually consists of either volumetric measuring or weighing of the product and diluting with a definite quantity of sterile water. This is followed by a shaking procedure, usually for a definite period of time, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1952
1952
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…As described above, a comparison was made of the bacterial counts obtained from samples prepared by blending and by shaking with glass beads. The present findings confirm observations by Jones and Ferguson (1951) that use of the blender method results in slightly higher counts. Coarse suspensions of shaken materials often furnish mechanical difficulties in transferring sample aliquots and lead to pipetting errors.…”
Section: Discussionsupporting
confidence: 92%
“…As described above, a comparison was made of the bacterial counts obtained from samples prepared by blending and by shaking with glass beads. The present findings confirm observations by Jones and Ferguson (1951) that use of the blender method results in slightly higher counts. Coarse suspensions of shaken materials often furnish mechanical difficulties in transferring sample aliquots and lead to pipetting errors.…”
Section: Discussionsupporting
confidence: 92%
“…Method of sample preparation. Various investigators (Jones and Ferguson, 1951;Zaborowski et al, 1958) have demonstrated that homogenization of the sample is preferable to shaking in bottles with diluent and glass beads in preparation of the initial dilution. Therefore, this variable was not included in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…A recent book on statistical methods (190) should also be of interest to food analysts. Methods of preparing food and plant products with the Waring Blendor, and the limitations of this equipment, have been discussed in three recent papers (90,131,148).…”
Section: Miscellaneousmentioning
confidence: 99%